Music, Authorship, and the Book in the First Century of Print. - Van Orden, Kate (University of California Press, 2013)
What does it mean to author a piece of music? What transforms the performance scripts written down by musicians into authored books? In this fascinating cultural history of Western music's adaptation to print, Kate van Orden looks at how musical authorship first developed through the medium of printing. When music printing began in the sixteenth century, publication did not always involve the composer: printers used the names of famous composers to market books that might include little or none of their music. Publishing sacred music could be career-building for a composer, while some types of.